Why Flesh? Examining the Power of Flesh in David Cronenberg’s The Fly - Shirley, Lea (East Carolina University)
This thesis is an exploration of body horror, specifically how one film's use of body horror impacts the body and the flesh within the body. "Why Flesh? Examining the Power of Flesh in David Cronenberg's The Fly is a close-viewing analysis of the film and how Cronenberg's carefully constructed film allowed for him to isolate the ways in which body horror truly terrifies audiences and forces them to confront themselves. Through the examination of flesh as it is impacted by pregnancy, aging, and chronic illness, The Fly acts as an excellent lens to discuss not only popular themes in body horror, but also get at the root of why they are horrifying.
Keywords: body horror; flesh; Cronenberg, David, 1943- . The fly; Horror films; Human body in motion pictures; Fear in motion pictures